2013
DOI: 10.1111/ajt.12244
|View full text |Cite
|
Sign up to set email alerts
|

What Liver Transplant Outcomes Can Be Expected in the Uninsured Who Become Insured via the Affordable Care Act?

Abstract: Our study objective is to measure the survival impact of insurance status following liver transplantation in a cohort of uninsured “Charity care” patients. These patients are analogous to the population who will gain insurance via the Affordable Care Act. We hypothesize there will be reduced survival in Charity care compared to other insurance strata. We conducted a retrospective study of 898 liver transplants from 2000–2010. Insurance cohorts were classified as Private (n=640), Public (n=233) and Charity care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…For example, HIV-infected individuals are disproportionately affected by poverty (9), which results in decreased access or utilization of health care, while transplant recipients are followed closely after transplantation, resulting in heightened medical surveillance. Further, in the U.S., HIV-infected people are less likely to have health insurance; one study of HIV-infected individuals in care reported that 28.4% were uninsured, compared to 2.6% of liver transplant recipients in another study (8;12). …”
Section: Discussionmentioning
confidence: 99%
“…For example, HIV-infected individuals are disproportionately affected by poverty (9), which results in decreased access or utilization of health care, while transplant recipients are followed closely after transplantation, resulting in heightened medical surveillance. Further, in the U.S., HIV-infected people are less likely to have health insurance; one study of HIV-infected individuals in care reported that 28.4% were uninsured, compared to 2.6% of liver transplant recipients in another study (8;12). …”
Section: Discussionmentioning
confidence: 99%
“…(513) With introduction of the ACA, there will be more Medicaid beneficiaries who can access organ transplantation, and given prior reports of inferior outcomes among this population, (5, 79) transplant centers may encounter observed survival rates significantly lower than expected. In the context of the current regulatory environment, understanding the impact of implementation of the ACA on transplant outcomes is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…With no insurance data available >5 years after LT, the analysis was limited to patients transplanted in 2009‐2013. LT performed in the postexpansion period were not analyzed due to potential changes in the composition of patients referred for LT in states where Medicaid expansion made LT available to more patients . Patients' state of residence was recorded at transplantation and during follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…Posttransplant enrollment in Medicaid may be an option for LT recipients who remain unemployed or otherwise experience difficulties with access to care due to low income. The availability of Medicaid for low‐income adults has been enhanced by the Patient Protection and Affordable Care Act (ACA) of 2010, designed to expand Medicaid by allowing eligibility at higher income levels and extending eligibility to adults with no children . Because this expansion of Medicaid did not take effect earlier than January 1, 2014 in most participating states, its effects on LT are uncertain, and at this time, are largely speculative …”
mentioning
confidence: 99%